1994
DOI: 10.1002/gps.930091004
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with recovery and recurrence of depression in older people: A prospective study

Abstract: SUMMARYThe Liverpool Continuing Health in the Community Study has followed up 1070 elderly community subjects over 6 years. In the first year 123 subjects had case-level depression. Three years later 49 (39.8%) of the previously depressed were recovered, 33 (26.8%) were depressed, 16 (13%) were not available for interview and 25 (20.3%) were dead. This study looks at factors associated with the 3-year outcome of patients who were depressed at year 0. Two outcome groups that were compared were a recovered depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…This may be related to undertreatment, as the two studies which reported the number of depressed people taking antidepressants both found very low rates (2/123, Green et al, 1994;and 11%, Livingston et al, 1997). Many older people living at home with anxiety and depression do not receive treatment for these disorders and do not improve with time alone.…”
Section: Outcome Of Affective Disorders In the Communitymentioning
confidence: 89%
“…This may be related to undertreatment, as the two studies which reported the number of depressed people taking antidepressants both found very low rates (2/123, Green et al, 1994;and 11%, Livingston et al, 1997). Many older people living at home with anxiety and depression do not receive treatment for these disorders and do not improve with time alone.…”
Section: Outcome Of Affective Disorders In the Communitymentioning
confidence: 89%
“…These pathways may be especially useful to maintain good levels of health and reduce the likelihood of health's deteriorating more so than influencing recovery once the level of health is more severe. Being married did not significantly influence one-year recovery from a state of exhaustion among older adults (Whitson et al 2011) or the recovery or recurrence of depression over three years among older adults (Green et al 1994). Married people had lower proportions of improvements in severity of disability over five years (Grundy and Glaser 2000), and marriage was not significantly associated with improvement in activities of daily living (ADL) in Israel or Italy (Gindin et al 2007).…”
Section: Marital Status and Healthmentioning
confidence: 99%
“…For example, whereas sleep disturbance has been shown to predict depression relapse and recurrence in late life (1116), these data are limited to convenience samples of specialty clinics. Other studies have examined factors associated with persistence of depression, as opposed to recurrence, in community-based older adults (1720), but none have tested the contribution of sleep disturbance. Moreover, in testing the association between sleep disturbance and late-life depression (i.e., including both first incidence and recurrence), no prior work took into account the role of other depressive symptoms and prior depression (2129).…”
mentioning
confidence: 99%